Dieciocho años de ciudadanía de la Unión: ¿hacia una figura emancipada? - Juárez Pérez, Pilar (CUADERNOS DE DERECHO TRANSNACIONAL, 2010)
Citizenship of the Union has been the subject of a new ruling of the ECJ, which dated March 10, 2010, has returned to rule on the controversial relationship than since its birth has established this figure with the nationality of the member States. This paper analyzes the decision from the perspective of the case law on this subject by examining its evolution and attempts to detect new considerations about the restrictions that Community law provides for regulations of nationality taken by member States. Just come of age, citizenship of the Union seems to attempt some emancipation from the rigid relationship of dependency to the State authority on nationality that it has maintained since its inception.